Amplifikasi DNA Kandidat Gen Kuda Pacu Sumba - Gaina, Cynthia Dewi; Francis, Frits B. H. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
The Sumba horse is one of the local horses in Indonesia which is known as racing horse Several candidate genes are known to influence the outward characteristics of the Sumba racehorse, which play main role in the development of the horse's muscles from embryo to adulthood. This research aims to identify candidate genes for the Sumba racehorse in stallion and mares. Blood samples from 5 stallions and 5 mares were collected and analyzed. The method used in this research was by using polymerase chain reaction (PCR), electrophoresis and DNA sequencing. The results of DNA amplification fragments at a temperature of 600c showed a fragment size of 463 bp. A total of 10 samples were sequenced on the PCR machine. The forward primer was 5'-TATTCTTCTTGGGAGGGAGGACTACT-3 'and reverse primer was 5'-GCAAGTAATTAGCACAAAAATTTGAATG-3'. The obtained data was analyzed using the Basic Local Alignment Sealing Tool (BLAST). Result of this study could be used as an initial identification of candidate genes for racing activity in stallion and mares that can complement the selection of racing horses.